2018
DOI: 10.1093/infdis/jiy499
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Markers for Ebolavirus Among Healthcare Workers in the Democratic Republic of the Congo

Abstract: Healthcare settings have played a major role in propagation of Ebola virus (EBOV) outbreaks. Healthcare workers (HCWs) have elevated risk of contact with EBOV-infected patients, particularly if safety precautions are not rigorously practiced. We conducted a serosurvey to determine seroprevalence against multiple EBOV antigens among HCWs of Boende Health Zone, Democratic Republic of the Congo, the site of a 2014 EBOV outbreak. Interviews and specimens were collected from 565 consenting HCWs. Overall, 234 (41.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…The Filovirus family consists of six widely recognised Ebolavirus species, with EBOV and Sudan ebolavirus (SUDV) being responsible for the majority of outbreaks in Africa. There is warranted concern that Marburg virus, another member of the filovirus family, may also cause serious disease outbreaks, with a recognition that cases may be under-reported as with other viral haemorrhagic fevers [3,4]. Cellular immunity was demonstrated to have a protective role during both Ebolavirus and Marburg virus (MARV) disease, and it was shown to be critically important in vaccine-mediated protection in macaques [5,6], although cross-strain cellular immune responses are difficult to identify.…”
Section: Introductionmentioning
confidence: 99%
“…The Filovirus family consists of six widely recognised Ebolavirus species, with EBOV and Sudan ebolavirus (SUDV) being responsible for the majority of outbreaks in Africa. There is warranted concern that Marburg virus, another member of the filovirus family, may also cause serious disease outbreaks, with a recognition that cases may be under-reported as with other viral haemorrhagic fevers [3,4]. Cellular immunity was demonstrated to have a protective role during both Ebolavirus and Marburg virus (MARV) disease, and it was shown to be critically important in vaccine-mediated protection in macaques [5,6], although cross-strain cellular immune responses are difficult to identify.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this theory, high levels of malarial parasitemia have been associated with higher total levels of IgG in children in The Gambia [34]. It should be highlighted that the study of Mc Elory and collaborators [32] [36] stated that the high proportion of anti-EBOV GP IgG might be due to unrelated nonspecific binding, with the high degree of glycosylation in EBOV GP lending itself to such nonspecific recognition. They also added that alternately, it might be that GP is more sensitive than other viral proteins to the presence of cross-reactive antibodies directed against related viruses.…”
Section: Anti-ebov Igg Antibody Activity Variation Related To Agementioning
confidence: 89%
“…A study of case contacts in Sierra Leone reported Ebola IgG seroprevalence at 11% [24]. In a recent study from Boende Health Zone in the DRC (site of the 2014 EVD outbreak) a range of serological tests were used to screen 565 health workers (not restricted to case contacts), among whom 234 (41.4%) were sero-reactive to at least one EBOV protein [25]. Among these cases, sera from a small minority (16) could neutralize a recombinant HIV virus expressing EBOV glycoprotein (GP).…”
Section: Ebola Transmission Dynamicsmentioning
confidence: 99%